The factors influence FDI to transfer into Vietnam - Thai, Hien Minh (2006)
Foreign direct investment (FDI) nowadays is increasing as one of important source to support for the economic growth in many countries especially for the developing countries. According to Hill (2005), he has acknowledged that the trend of FDI transferring into developing countries is increasing. Among the Asia, China, India, Korea, Taiwan and South East Asia are among the most attractive destination for FDI to enter. These places have some kinds of comparative advantages that not many other places can have the same characteristics. Vietnam is among this region so absolutely they also can inherit some factors like the other countries and some specific characteristics that only Vietnam can possess. Vietnamese government has recognized the important role of FDI so long time. The government had created Foreign Investment law since 1986 to facilitate the investment from the foreign source. However, the actual influence of FDI really starts to happen only beginning from 1996 with the revised of investment law and applying the Doi moi program effectively. Vietnam has started to use its comparative advantages to attract FDI to support for the economic growth and improve social welfare. Along with promoting the advantage factors to lure FDI into Vietnam, the government also creates the suitable and useful policies to upgrade its advantage factors and up the positive factors that it has already possess. Even though Vietnam has received very attractive achievements in term of economic growth, many experts still believe that Vietnam is still far behind the real potential of attracting economic growth. Vietnam still has some limitations that the government needs to identify and fix it immediately. If they are not fixed it a short time, the specific steps must be progressed to gain the reputation and optimistic from the foreign investors to continue investing in Vietnam. Therefore, along with the comparative advantages that Vietnam is already having, the government also needs to use specific actions to reduce the barriers and limitations that foreign investors are encountering. Only by doing that Vietnam can guarantee that there will be more opportunities for foreign investors in the future and can exploit the potential of Vietnamese market at full potential.